INTEGRATIVE STRATEGY IN STRENGTHENING MSME COMPETITIVENESS: THE ROLE OF LOCALLY ROOTED ENTREPRENEURIAL VALUES IN BUILDING SUSTAINABLE COMPETITIVE ADVANTAGE - Sutrisno, Sutrisno; Mustafa, Fahrina; Mersandro Permana, Riko (Technopreneurship and Educational Development Review (TENDER), 2025)
This study aims to examine integrative strategies for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), focusing on the role of locally rooted entrepreneurial values as a foundation for building sustainable competitive advantage. Using a qualitative approach and literature review method, this research analyzes 19 selected scholarly articles published between 1978 and 2025, sourced from Google Scholar and reputable academic websites. The analysis reveals that local values such as gotong royong (mutual cooperation), honesty, traditional trade ethics, and community solidarity serve as highly strategic intangible resources in shaping authentic business identity, product differentiation, and customer loyalty. Integrative strategies that combine these values with digital innovation, modern marketing, and sustainability orientation have proven effective in enhancing MSME competitiveness amid globalization pressures. Case studies of various MSMEs in Indonesia support the argument that the strategic management of local values not only strengthens social and cultural ties but also creates unique value propositions in the market.